On COVID-19 outburst and smart city/urban system connection: worldwide sharing of data principles with the collaboration of IoT devices and AI to help urban healthiness supervision and monitoring - Jabbar, Jahangir; Mehmood, Hussain; Hafeez, Umaima; Malik, Hassaan; Salahuddin, Humayun (International Journal of Engineering and Technology, 2020)
Every one of us knows about the rise of Coronavirus (COVID-19) from Wuhan (China) and its effects into nearby states and further motherlands, increased domestic and worldwide methods are being occupied to contain the outburst. In terms of Economic and Social point of view, it directly disturbs the metropolitan markets on a high level by engaging all the capitals and towns in a lock-down situation. Itâ€™s also highlighted if this situation increases in different countries then it can lead in a direction to world-wide health disaster and in many accommodations as well. Be that as it may, while compelling conventions concerning the sharing of good information is underscored, urban information, then again, explicitly identifying with urban well-being and safe city ideas, is still seen from a patriot point of view as exclusively profiting a country's economy and its monetary and political impact. This article will explore the new and better universal understandings and also shows how smart city/urban systems be able to improve uniform procedures for bigger data sharing in the time of tragedies.Â Â